Enhancing VANET Mobility Management Through Intelligent Relay Vehicle Optimization (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Vehicular Ad Hoc Networks (VANETs) play a crucial role in enabling intelligent transportation systems by supporting real-time vehicle-to-vehicle and vehicle-to-infrastructure communications. However, high node mobility, frequent topology changes, and intermittent connectivity significantly affect communication reliability and network performance. To address these challenges, this paper proposes an intelligent relay vehicle optimization approach aimed at enhancing mobility management in VANET environments. The proposed scheme dynamically selects optimal relay vehicles based on key parameters such as vehicle mobility patterns, relative speed, link stability, and network connectivity conditions. By intelligently adapting to rapidly changing vehicular scenarios, the approach improves data forwarding efficiency, reduces packet loss, and enhances overall communication reliability. Simulation-based performance evaluation demonstrates that the proposed method outperforms conventional relay selection techniques in terms of packet delivery ratio, end-to-end delay, and network throughput. The results indicate that intelligent relay vehicle optimization is an effective solution for robust and efficient mobility management in VANETs, particularly in high-speed and dense traffic conditions.